Interview with César Cabezas - Reyes, Esperanza (2000)
Dr. César Cabezas is a prominent researcher at the National Institute of Health who has conducted several valuable investigations, including studies on yellow fever, dengue, viral hepatitis, and malaria. His training as a professional began at the University of San Marcos, where he graduated as a medical surgeon in 1985. Later, he obtained a specialization in infectious and tropical diseases and a master's degree in medicine from the Universidad Peruana Cayetano Heredia. He has been director general of the National Center for Public Health Laboratories between 1994 and 1998.